The Influence of Green Competitive Advantage to Value Relevance of Earning and Book Value - Rachmawati, Sistya; Murwaningsari, Etty; Augustine, Yvonne (IJOSMAS, 2022)
The purpose of this study is to analyze the empirical evidence of the effect of green competitive advantage on the value relevance of earnings and book value in terms of the stock price model and the cumulative abnormal return model (return model). The data used in this study is secondary data derived from annual reports and sustainability reports listed on the IDX-IC (IDX Industrial Classification) and taken from the Indonesia Stock Exchange (IDX) through the website (www.idx-ic.co .id). The research sample was taken by purposive sampling with a total of 110 observations. The results showed a significant positive effect of green competitive advantage on the value relevance of earnings, both the price model and the return model. Thus, information is said to be relevant if information on green competitive advantage can contribute to profits and react positively to the market, so that it can be used as a basis for decision making. The test results show that there is no significant negative effect for green competitive advantage on the value relevance of book value with the price model. However, the green competitive advantage for the return model has a significant negative effect on the value relevance of book value. These results indicate that investors fail to recognize the potential book value in the future. Thus the information is said to be irrelevant because the green competitive advantage information reflected in the book value is not responded to by the market. The results of this study indicate that the value relevance of earning and book value is non-linear.